PENGEMBANGAN MEDIA PAPAN DAILY NUMBER PADA PEMBELAJARAN MATEMATIKA MATERI PENJUMLAHAN DAN PENGURANGAN KELAS II SD - Juliani br Sembiring; Umar Darwis (STKIP Subang, 2024)
This research is a type of research and development using the ADDIE model, namely analysis, design, development, implementation and evaluation. But researchers only reached development. The subjects in this research were daily number board media, class II elementary school teachers, media expert validation, material experts and the objects in this research were daily number board media in mathematics learning with addition and subtraction material, namely class II elementary school students. Quantitative data is obtained from the formula used to determine the suitability of media and materials. The data obtained is used as a reference for making revisions to the products being developed. Based on the calculations above, the results of the overall assessment of the material experts reached the instrument used to collect data, namely a questionnaire. The results of the validation of the daily number board media in mathematics learning on addition and subtraction material are that the media expert validation obtained a score of 92% with the criteria being very suitable for use and suitable for development in mathematics learning on addition and subtraction material which is very feasible, the material expert validation obtained a score of 80% with the appropriate criteria used, the teacher's response obtained a score of 67% with the criteria being suitable for use and the validation class teacher obtained a score of 100% with the criteria being very feasible. Based on the data obtained, it can be concluded that the daily number board media is very suitable for use in elementary schools